Duodenal diverticulum: incidental finding with potentially dangerous outcomes. Issue 1 (2nd January 2017) - Melnick, Stephen; Fareedy, Shoaib; Gish, David; Nazir, Salik
ABSTRACT: We present the case of an 83-year-old woman with a past medical history significant for schizoaffective disorder, presenting to our emergency department with the complaint of 'pain'. Given the non-specific complaint and the limited history obtained, CT imaging was performed on her chest and abdomen which incidentally found a large duodenal diverticulum. This manuscript discusses the incidence of duodenal diverticula and the potential associated complications.